Análise do exercício profissional do assistente social na política de assistência estudantil da Universidade Federal de Sergipe - Ananias, Danielle Lima Menezes (2019)
This dissertation aims to study the professional practice of the social worker in the student assistance policy of the Federal University of Sergipe (UFS), based on the National Program of Student Assistance (PNAES). The proposed research is based on the dialectical method, with an exploratory character with a qualitative approach, and has as a research subtype the case study. Thus, to support the construction of the theoretical path and acquisition of information on the theme, different sources of information were used: bibliographical sources supported in literature review and authors' contribution on the subject, through books, articles and researches. In addition to the documentary sources constituted by: National Program of Student Assistance, Management reports, UFS regulatory acts, and laws regarding education policy and Social Work, used to carry out the historical rescue. Thus, during the course of the study, the general aspects of education policy in Brazil were rescued; the historical trajectory of student assistance, establishing connections with the economic, social and political determinants and the PNAES, as well as an analysis of the meaning of the profession and its legitimation for a better understanding of the social historical foundations of Social Work in capitalist society, the contextualization of the constitutive dimensions of professional practice and the role of the social worker in the politics of student education and assistance. The empirical field encompasses the social workers who work on the various UFS campuses and the sample represented more than 50% of the research universe. For the data collection, a questionnaire was applied with the social workers, subjects of the research, elaborated according to the general and specific objectives of the research. From the answers of the seven (07) seven social workers who answered the questionnaire, the results of the research were presented. The responses revealed that the activities described are essentially conditioned to the actions that allow or deny access to student assistance policy, placing socioeconomic analysis as the main demand, although the PNAES does not officially limit the work of the social worker to this role as a job description and MPOG activities. Despite this, the work routine is absorbed by spontaneous and emergency demands, benefits administration and socioeconomic analysis. It was noticed the discomfort of the professionals with the prevalence of administrative activities that limit the follow-up to the students, as well as the work planning. In addition to the concern with the quality of services provided, from the point of view of social rights, it is possible to visualize other possibilities of intervention that are and / or can be constructed, through a correlation of present forces and the relations built in the institutional daily life. Finally, it was verified that the professional practice of social workers is in line with the provisions of the Professional Code of Ethics.